Efforts to Reduce Headache in Grade II Tuberculosis Meningitis Patients: A Case Study - Suhendar, Ryzka Fridekia; Hartati, Sri; Komariah, Maria (Journal of Nursing Care, 2024)
Tuberculous meningitis is a life-threatening disease and can cause severe manifestations and neurological disorders. Headache is one of the symptoms that occurs in patients with tuberculosis meningitis. An 18-year-old woman was admitted with complaints of unilateral headache in the holocranial region with a description of throbbing pain on a scale of 6 (0-10), which decreases when she closes her eyes and sleeps. The pain is felt continuously and slightly interferes with activities. This case study aim to describe intervention that can reduce headache in Grade II Tuburculosis Meningitis. Nursing actions are given to minimize the pain experienced by patients with tuberculosis meningitis, namely carrying out pharmacological and non-pharmacological pain management by collaborating in giving paracetamol 500 mg and teaching non-pharmacological pain management by facilitating patient rest, teaching deep breathing relaxation. In addition, immediate treatment is needed by administering anti-tuberculosis drugs (OAT) and corticosteroids. Corticosteroids are given to minimize complications and death rates by suppressing the inflammatory response in the subarachnoid space. After being given care, the problem of acute pain is partially resolved so that further treatment is needed with participation of the patient and family for the success of nursing care. It is necessary to improve pain management in treating patients with TB meningitis headaches.